Active Repertoires to “decir la guerra”: The Case of Bajo la Tienda (1890) by Daniel Riquelme and Sancho en la guerra (1885) by Lucio Venegas - Véliz Rojas, Claudio (2024)
The present work applies the theoretical framework of polysystems, by Itamar Evan-Zohar, and its concretization through the transtextuality approaches of Gérard Genette, to analyze the “active repertoires” of two works written by Chilean actors of the War of the Pacific (1879- 1884) published during the 1880s. Through Bajo la Tienda (1890) by Daniel Riquelme and Sancho en la guerra (1885) by Lucio Venegas, we recognize the use of these repertoires as ways to glorify the conflict while also serving as formulas to condemn the destruction caused by the war phenomenon. These repertoires help us understand the cultural landscape of the time as an active agent in the construction of a certain notion of war.